2021
DOI: 10.1002/ehf2.13193
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial deformation assessed among heart failure entities by cardiovascular magnetic resonance imaging

Abstract: Aims Although heart failure (HF) is a leading cause for hospitalization and mortality, normalized and comparable non-invasive assessment of haemodynamics and myocardial action remains limited. Moreover, myocardial deformation has not been compared between the guideline-defined HF entities. The distribution of affected and impaired segments within the contracting left ventricular (LV) myocardium have also not been compared. Therefore, we assessed myocardial function impairment by strain in patients with HF and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…During stress the impaired septal segments improved primarily in terms of circumferential strain ( Figure 1B ). It has been shown that septal impairment precedes global systolic dysfunction, highlighting the relevance of septal assessments in the future ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During stress the impaired septal segments improved primarily in terms of circumferential strain ( Figure 1B ). It has been shown that septal impairment precedes global systolic dysfunction, highlighting the relevance of septal assessments in the future ( 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study was a prospective study conducted in Berlin, Germany, approved by the local Ethics Committee (registration: EA4/112/16; German Clinical Trials Registry, DRKS, DRKS00015615). Its rationale and design have been described previously ( 10 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations